Encyclopedia of Electrochemistry 2003
DOI: 10.1002/9783527610426.bard030207
|View full text |Cite
|
Sign up to set email alerts
|

The Electrochemical Quartz Crystal Microbalance

Abstract: This chapter reviews the development and use of the electrochemical quartz crystal microbalance (EQCM) as an in situ probe of interfacial processes involving the formation, properties, and redox switching of multilayer films. For films that are sufficiently rigid and/or thin (termed acoustically thin ), the EQCM functions as a quantitative gravimetric probe of surface population changes. This well‐established methodology is now being used to explore both thermodynamic and kinetic aspect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 169 publications
0
27
0
Order By: Relevance
“…Detailed structure and composition depend on deposition conditions, notably electrode material, solvent, pH, temperature and control function [4,20,22]. We note that the EQCM [23,24], yields changes in film mass and thus changes in mobile species populations, but not absolute populations. When the observational timescale is shorter than the equilibration timescale, such that repetitive cycling results in a ratchetting of mobile species populations [25,26], rationalisation of film responses becomes extremely complicated [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Detailed structure and composition depend on deposition conditions, notably electrode material, solvent, pH, temperature and control function [4,20,22]. We note that the EQCM [23,24], yields changes in film mass and thus changes in mobile species populations, but not absolute populations. When the observational timescale is shorter than the equilibration timescale, such that repetitive cycling results in a ratchetting of mobile species populations [25,26], rationalisation of film responses becomes extremely complicated [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to studying the ion movement in dependence of the redox state, viscoelastic properties of polymer films have been investigated with EQCM impedance studies in respect to redox state in various films [58]. For example, EQCM impedance studies of Os(byp) 2 ClPyCH 2 NH 2 -poly(allylamine)hydrogel (Os-PAA) cross-linked with glucose oxidase (GOx) revealed that swelling of the film during Os II oxidation resulted in a mass uptake and a decrease of shear modulus [61].…”
Section: Tablementioning
confidence: 99%
“…The deviation from the linearity regarding the m vs. Q function is related to the appearance of the viscoelastic effect. By the help of impedance measurements the viscoelastic characteristics of the surface film can also be tested [4,5,6,7,10]. In the absence of any deposition the change of the density and viscosity in the double layer or in the diffusion layer may cause 0.1-10 Hz frequency change.…”
Section: Ii1023 the Electrochemical Quartz Crystal Nanobalance (Eqcn)mentioning
confidence: 99%